Antibiotic Therapy for Active Crohn's Disease Targeting Pathogens: An Overview and Update - Gaetano Iaquinto; Giuseppe Mazzarella; Carmine Sellitto; Angela Lucariello; Raffaele Melina; Salvatore Iaquinto; Antonio De Luca; Vera Rotondi Aufiero (MDPI AG, 2024)
Crohn's disease (CD) is a multifactorial chronic disorder that involves a combination of factors, including genetics, immune response, and gut microbiota. Therapy includes salicylates, immunosuppressive agents, corticosteroids, and biologic drugs. International guidelines do not recommend the use of antibiotics for CD patients, except in the case of septic complications. Increasing evidence of the involvement of gut bacteria in this chronic disease supports the rationale for using antibiotics as the primary treatment for active CD. In recent decades, several pathogens have been reported to be involved in the development of CD, but only Escherichia coli (E. coli) and Mycobacterium avium paratubercolosis (MAP) have aroused interest due to their strong association with CD pathogenesis. Several meta-analyses have been published concerning antibiotic treatment for CD patients, but randomized trials testing antibiotic treatment against E. coli and MAP have not shown prolonged benefits and have generated conflicting results; several questions are still unresolved regarding trial design, antibiotic dosing, the formulation used, the treatment course, and the outcome measures. In this paper, we provide an overview and update of the trials testing antibiotic treatment for active CD patients, taking into account the role of pathogens, the mechanisms by which different antibiotics act on harmful pathogens, and antibiotic resistance. Finally, we also present new lines of study for the future regarding the use of antibiotics to treat patients with active CD.